A method for in-situ control of nano-powder cluster particle size
Patent Information
- Application Number
- CN202611419005.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-14
- Publication Date
- 2026-10-16
AI Technical Summary
[0003]然而,纳米粉末团簇粒径越小,颗粒间的分子间作用力越强,极易发生团聚
[0019] In step four of the above method, the heat treatment should involve placing the nanoparticle clusters inside a refractory container and pre-treating them using a micro-press to ensure full contact between the powders.
Smart Images

Figure CN122913493A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of new material nanopowder cluster technology, specifically relating to a method for in-situ control of nanopowder cluster particle size. Background Technology
[0002] In fields such as new energy and power equipment, with the continuous expansion of application scenarios and the sustained improvement of performance requirements, existing equipment is facing increasingly severe performance bottlenecks. Whether it's the energy density limit of lithium batteries, the catalyst lifetime of fuel cells, or the power density of capacitors, traditional micron-scale material systems are struggling to meet the demands for miniaturization, high capacity, and high reliability. In recent years, nanoparticle cluster materials have shown great potential in overcoming these performance bottlenecks due to their unique quantum size effect and high specific surface area. Taking multi-layer ceramic capacitors (MLCCs) as an example, nickel powder, as the internal electrode material, directly determines the electrode layer thickness and the device's electrical performance. As MLCCs rapidly develop towards miniaturization and high capacitance, stringent requirements are placed on nickel powder for extremely fine particle size, high crystallinity, and high dispersibility. Research shows that using 200 nm nickel powder can increase capacitance by 2% compared to 400 nm products, while significantly increasing internal resistance by 60%; and homogenized extremely fine nickel powder can further improve MLCC lifetime stability by 3 times and reduce the incidence of tip discharge by 90%. This indicates that precisely controlling the particle size of nanoparticle clusters is a key technological path to achieving performance breakthroughs in high-end power equipment.
[0003] However, the smaller the particle size of nanoparticle clusters, the stronger the intermolecular forces between the particles, making them highly prone to agglomeration. In MLCCs, once the nickel powder in the internal electrode is unevenly dispersed and forms agglomerates, it can lead to localized breakdown of the ceramic dielectric layer, causing device failure. Currently, the mainstream preparation methods for nickel powder in MLCC internal electrodes include liquid-phase chemical methods (such as CN 121339465 A) and plasma methods (such as CN 119407182 A). These methods still face many challenges in terms of the precision of particle size control, the uniformity of particle size distribution, and batch stability, making it difficult to meet the technical requirements of MLCCs developing towards thinner dielectric layers and higher capacitance values. The above problems are also common in nanoparticle clusters used in other new energy power equipment (such as silicon anodes and platinum catalysts). Therefore, it is urgent to develop a method that can precisely control the particle size of nanoparticle clusters in situ to effectively suppress agglomeration, ensure high purity and batch consistency, thereby breaking through technical bottlenecks such as MLCC internal electrode materials and meeting the urgent needs of high-end electronic components and the new energy industry for high-performance nanoparticle clusters. Summary of the Invention
[0004] The technical problem this invention aims to solve is to address the shortcomings of the prior art by providing a method for in-situ control of nanopowder cluster particle size. This invention employs a high-vacuum interconnected inert gas condensation system, using picosecond lasers to bombard a bulk target to generate nanoclusters. These clusters are collected in a liquid nitrogen cold trap and transferred to a glovebox with a water and oxygen content below 1 ppm. The glovebox utilizes a programmable infrared heating device (temperature limit 1000℃) to perform in-situ heat treatment of the nanopowder clusters, while simultaneously using a micro-press for pretreatment to ensure sufficient powder contact. This method can achieve precise in-situ control of the particle size of nanoclusters of different compositions, including elemental metals, binary alloys, ternary and higher entropy alloys, amorphous alloys, and ceramics, while maintaining high purity of the nanopowder clusters. It effectively suppresses agglomeration, significantly improves the uniformity of particle size distribution and batch stability, meeting the urgent demand for ultrafine nanopowders in high-end electronic components. This method is not only fast and efficient but also offers significant economic benefits.
[0005] To solve the above-mentioned technical problems, the technical solution adopted by the present invention is as follows:
[0006] A method for in-situ control of nanopowder cluster particle size, wherein the nanoclusters include elemental metals, binary alloys, ternary and above medium-high entropy alloys, amorphous alloys and ceramics prepared by inert gas condensation, and the particle size of the nanoclusters is controlled by a vacuum in-situ integrated infrared heating device.
[0007] Furthermore, this invention also discloses a specific process for implementing the above-mentioned in-situ particle size control method for nanopowder clusters, the method comprising the following steps:
[0008] Step 1: Place the bulk target material of the high-purity target component nanoparticle clusters into a high-vacuum interconnected inert gas condensation system, and wait for the system vacuum to reach 10... -6 After Pa, an inert gas at a certain pressure is injected.
[0009] Step 2: After liquid nitrogen is injected into the powder cluster collection cold trap, the picosecond laser heat source is turned on to bombard the target material by adjusting different powers.
[0010] Step 3: Collect the powder using a rotating cold trap and scraper, and transfer the nanopowder clusters into the glove box using a built-in robotic arm;
[0011] Step 4: In-situ heating treatment of different types of nanopowder clusters at 600-1000℃ is carried out using the built-in intelligent infrared heating system in the glove box.
[0012] In the above method, in step one, the bulk target material can be flexibly selected according to the composition of the target nanopowder, specifically including: pure metal targets such as nickel, copper, silver, platinum, gold, iron, cobalt, chromium, molybdenum, tungsten, etc.; binary alloy targets such as Ni-Fe, Cu-Ag, Pt-Ru, Au-Cu, etc.; ternary and higher entropy alloy targets such as CoCrFeNi, AlCoCrFeNi, CrMnFeCoNi, etc.; amorphous alloy targets such as Zr-Cu, NiMoNb, Fe-B, etc.; and ceramic targets such as SiC, Al2O3, TiO2, ZnO, etc. The density and purity of the target material directly affect the generation efficiency and compositional uniformity of the nanoclusters; therefore, high-density (relative density ≥98%) and high-purity (≥99.9%) targets are preferred.
[0013] In the above method, step one, the pressure of the inert gas is one of the key parameters for controlling the particle size of the nanoclusters. In this invention, the adjustable range of the inert gas pressure is 50 Pa to 5000 Pa. Experiments show that when the inert gas pressure is low (e.g., 50~2000 Pa), the atoms or clusters generated by laser bombardment travel a longer distance in the gas phase and have a lower collision frequency, which is beneficial for forming nanoclusters with smaller particle sizes. Under these conditions, nanoclusters with sizes greater than 10 nm and less than 15 nm are prepared.
[0014] When the inert gas pressure is high (e.g., 2000~5000 Pa), the collision frequency between atoms or clusters and gas molecules increases, the cooling rate accelerates, and it is easier to form nanoclusters with larger particle sizes. Under these conditions, nanoclusters with sizes greater than 15 nm and less than 20 nm can be prepared. The inert gas pressure can be flexibly selected within this range according to the actual target particle size requirements to initially control the initial nanocluster particle size.
[0015] In the above method, step one uses inert gases including helium, argon, and nitrogen.
[0016] In the above method, in step two, the power of the picosecond laser heat source bombarding the target material is 20~72 kW. Lower laser power (20~50 kW) is suitable for targets with low melting points or easy evaporation, which can produce finer nanoclusters (such as metals and their alloys such as Ni, Fe, Co, Cr, etc.); higher laser power (50~72 kW) is suitable for targets with high melting points or difficult evaporation (such as tungsten, molybdenum or ceramics) to ensure sufficient evaporation rate and nanocluster yield.
[0017] In the above method, step three ensures that the water and oxygen content inside the glove box is below 1 ppm. Combined with contactless transfer using a robotic arm, this guarantees that the nanopowder remains oxidation-free and pollution-free throughout the entire process from generation to heat treatment, ensuring the high purity and excellent performance of the final product. Preferably, the glove box is equipped with both oxygen and moisture sensors for real-time monitoring and features an automatic circulation and purification system.
[0018] In step four of the above method, the infrared heating device is built into the glove box. This device uses a high-efficiency infrared radiation heating element, enabling precise program-controlled heating, holding, and cooling processes, and supports multi-segment temperature curve settings. Its maximum heating temperature can reach 1000℃, meeting the heat treatment requirements (such as annealing, crystallization, and surface passivation) of most metal, alloy, and ceramic nanopowders. Through in-situ infrared heating, the grain size of nanoclusters can be precisely controlled, thereby indirectly controlling the surface morphology and internal defects, achieving precise in-situ control of particle size. Temperature can be monitored and adjusted in real time during the heating process, and the heating rate can be arbitrarily set within the range of 1~30℃ / min.
[0019] In step four of the above method, the heat treatment should involve placing the nanoparticle clusters inside a refractory container and pre-treating them using a micro-press to ensure full contact between the powders.
[0020] This invention utilizes a combination of high-vacuum inert gas condensation, picosecond laser bombardment, liquid nitrogen cold trap collection, glove box protection, and in-situ infrared heating for heat treatment. By controlling the inert gas pressure, laser power, and infrared heat treatment program, it achieves precise in-situ control of the particle size of nanoparticle clusters with different compositions. This method effectively avoids the problems of uncontrollable particle size, easy agglomeration, impurity contamination, and poor batch stability in traditional preparation processes. Furthermore, because the infrared heating device is integrated into the glove box, the entire process can be handled in-situ without exposing the powder to the atmosphere, ensuring the high purity and excellent performance of the nanoparticles. This method features a continuous process, a wide range of adjustable parameters, and strong versatility, solving the technical challenges of precise particle size control, uniform distribution, and large-scale production in existing nanoparticle preparation technologies.
[0021] The technical solution of the present invention will be further described in detail below with reference to the accompanying drawings and embodiments. Attached Figure Description
[0022] Figure 1 This is a statistical analysis of the particle size of the nano-Ni powder clusters prepared in Example 1 of the present invention.
[0023] Figure 2 This is a statistical analysis of the particle size of nano-Ni powder clusters treated at 600℃ in Example 1 of the present invention.
[0024] Figure 3 This is a statistical analysis of the particle size of nano-Ni powder clusters treated at 600℃ in Example 2 of the present invention.
[0025] Figure 4 This is a statistical analysis of the particle size of nano-Ni powder clusters treated at 500℃ in Example 3 of the present invention.
[0026] Figure 5This is a statistical analysis of the initial state nano-Fe-Ni powder cluster size in Example 4 of the present invention.
[0027] Figure 6 This is a statistical analysis of the particle size of nano-Fe-Ni powder clusters treated at 900℃ in Example 4 of the present invention. Detailed Implementation
[0028] Example 1
[0029] The nanopowder clusters selected in this embodiment are elemental Ni, which are treated by in-situ infrared heating at 600°C for 5 min.
[0030] The method for preparing Ni nanopowder clusters in this embodiment includes the following steps:
[0031] Step 1: Place the high-purity elemental Ni target (99.99 at.%) into a high-vacuum interconnected inert gas condensation system (team-developed equipment, used for nanopowder preparation and in-situ ultra-high pressure forming high-vacuum interconnected system, ZL 2018 10407710.4), and wait for the system vacuum to reach 10. -6 After Pa, 500 Pa of helium gas is introduced. The nanoclusters prepared based on this pressure generally have a smaller particle size (less than 15 nm), which is more suitable for subsequent comparison of particle size control effects.
[0032] Step 2: After liquid nitrogen is injected into the powder cluster collection cold trap, the picosecond laser heat source is turned on to bombard the target material. Given that the saturated vapor pressure of Ni target material is relatively low (but still significantly higher than that of refractory metals such as tungsten and molybdenum), a laser power of 30 kW is sufficient to create a sufficient temperature rise on the target surface to maintain a stable evaporation rate. This power ensures sufficient cluster yield while avoiding excessive gas phase supersaturation and widening of particle size distribution caused by excessive power.
[0033] Step 3: Collect the powder using a rotating cold trap and scraper. Once the powder container is full, transfer the Ni nanopowder clusters to the glove box using a built-in robotic arm.
[0034] Step 4: The nanopowder clusters are simply compacted using a built-in small press (10 MPa) to increase the contact area between particles; different types of nanopowder clusters are in-situ heated using an intelligent infrared heating system built into the glove box (an infrared oven heating module structure, ZL 2024 22979038.X). The infrared irradiation temperature is set to 600℃, the heating rate is 10℃ / min, and the holding time is 5 min.
[0035] TEM particle size observation was performed on the Ni nanopowder clusters in the prepared state and the infrared heat-treated state of this embodiment. The results showed that the average grain size of the Ni nanopowder clusters prepared in this embodiment was 14.5 nm. After infrared heat treatment at 600℃ for 5 min (600℃ is approximately 0.5 times the melting point T), the particle size of the Ni nanopowder clusters was significantly reduced. m The average grain size grew to 19 nm. Infrared heating at 600℃ activated the surface atomic diffusion of the nano-Ni clusters. Through the Ostwald ripening mechanism, small particles dissolved / evaporated, large particles continued to grow, and grain boundaries between adjacent particles merged, allowing the average grain size to grow controllably from 14.5 nm to 19 nm. The uniform temperature field characteristics of infrared heating effectively avoided abnormal growth and ensured the narrowing of the grain size distribution.
[0036] Figure 1 For the statistical analysis of the particle size of the nano-Ni powder clusters prepared in this embodiment, from... Figure 1 It can be seen that the average grain size of the prepared Ni nanopowder clusters is 14.5 nm.
[0037] Figure 2 This example presents the particle size statistics of nano-Ni powder clusters treated at 600℃ in this embodiment. Figure 2 It can be seen that the average grain size of the Ni nanopowder clusters after infrared heat treatment at 600℃ for 5 min is 19 nm.
[0038] Example 2
[0039] The nanoparticle clusters selected in this embodiment are elemental Ni, which are treated by in-situ infrared heating at 800°C for 5 min. This embodiment is mainly used to compare the particle size growth of Ni nanoparticle clusters at higher temperatures.
[0040] Steps one, two, and three of this embodiment are the same as those of embodiment 1. The difference is that in step four, the nanopowder clusters are simply compacted by a built-in small press (10 MPa) to increase the contact area between particles; and different types of nanopowder clusters are in-situ heated by the built-in intelligent infrared heating system in the glove box. The infrared irradiation temperature is set to 800℃ and the holding time is selected as 5 min.
[0041] TEM particle size analysis was performed on the Ni nanopowder clusters in the prepared state and the infrared heat-treated state of this embodiment. The results showed that the average grain size of the Ni nanopowder clusters prepared in this embodiment was 14.5 nm. The particle size was measured at 800℃ (approximately 0.6 times the melting point T). mAfter infrared heat treatment for 5 min (heating rate of 10℃ / min), the average grain size grew to 25 nm. This is significantly larger than at 600℃ (14.5 nm → 19 nm). The fundamental reason is that the increase in temperature causes an exponential increase in the surface diffusion coefficient of Ni atoms and the grain boundary migration rate (Arrhenius relationship), accelerating the Ostwald ripening process and the merging and growth of adjacent particles; simultaneously, 0.6 T m The temperature range is close to the intermediate temperature sintering region, allowing for more complete atomic rearrangement and structural relaxation. The uniform temperature field of infrared heating ensures that this accelerated growth process is still achieved in a controllable manner, without any abnormal grain growth.
[0042] Figure 3 For the particle size statistics of nano-Ni powder clusters treated at 800℃ in this embodiment, such as... Figure 3 The average grain size of Ni nanopowder clusters after infrared heat treatment at 800℃ for 5 min is 25 nm.
[0043] Example 3
[0044] In this embodiment, the selected nanoparticle clusters are elemental Ni, which are treated by in-situ infrared heating at 500°C for 5 min. This embodiment is mainly used to explore the lower limit temperature at which infrared treatment temperature affects particle size control.
[0045] Steps one, two, and three of this embodiment are the same as those of embodiment 1. The difference is that in step four, the nanopowder clusters are simply compacted by a built-in small press (10 MPa) to increase the contact area between particles; and different types of nanopowder clusters are heated in situ by a built-in intelligent infrared heating system in the glove box. The infrared irradiation temperature is set to 500℃ and the holding time is selected as 5 min.
[0046] TEM particle size observation of the Ni nanopowder clusters in the infrared heat-treated state of this embodiment showed that after infrared heat treatment at 500℃ for 5 min (heating rate of 10℃ / min), the average grain size was 14.8 nm, which remained almost unchanged compared to the prepared state. This is because this temperature has not yet reached the thermal activation threshold for significant surface diffusion and grain boundary migration of Ni atoms, thus limiting long-range atomic migration. This indicates that 500℃ does not meet the minimum temperature requirement for particle size growth, providing a lower limit for the temperature window for subsequent controllable growth at higher temperatures.
[0047] Figure 4 The particle size statistics of the nano-Ni powder clusters treated at 500℃ in this embodiment are as follows: Figure 4 The average grain size of the Ni nanopowder clusters after infrared heat treatment at 500℃ for 5 min remained almost unchanged at 14.8 nm.
[0048] Example 4
[0049] The nanoparticle clusters selected in this embodiment are binary Fe-Ni. This embodiment is mainly used to illustrate the applicability of this particle size control process in other systems and to explore the particle size control effect brought about by higher infrared processing temperatures.
[0050] The Fe-Ni nanopowder cluster preparation method in this embodiment includes the following steps:
[0051] Step 1: Place the high-purity binary Fe-Ni alloy target (99.99 at.%) in a high-vacuum interconnected inert gas condensation system, and wait for the system vacuum to reach 10... -6 After Pa, 200 Pa of helium gas is introduced;
[0052] Step 2: After liquid nitrogen is injected into the powder cluster collection cold trap, the picosecond laser heat source is turned on to bombard the target material. Here, the laser power is selected as 40 kW, which is higher than the 30 kW of the pure Ni target material in Example 1. The reason is that the saturated vapor pressure of Fe in the binary Fe-Ni alloy is lower than that of Ni. Higher power is needed to increase the surface temperature of the target material so that the evaporation rate of Fe matches that of Ni. This avoids insufficient Fe evaporation at low power, which would cause the cluster composition to be biased towards Ni, and ensures a high degree of consistency between the cluster composition and the target material composition.
[0053] Step 3: Collect the powder using a rotating cold trap and scraper. Once the powder container is full, transfer the Fe-Ni nanopowder clusters to the glove box using a built-in robotic arm.
[0054] Step 4: The nanopowder clusters are simply compacted using a built-in small press (10 MPa) to increase the contact area between particles; different types of nanopowder clusters are in-situ heated using the built-in intelligent infrared heating system in the glove box. The infrared irradiation temperature is set to 900℃, the heating rate is 10℃ / min, and the holding time is 5 min.
[0055] TEM particle size observation was performed on the Fe-Ni nanopowder clusters in the prepared state and the infrared heat-treated state of this embodiment. The results showed that the average grain size of the Fe-Ni nanopowder clusters in the prepared state of this embodiment was 13.3 nm, which was slightly lower than the 14.5 nm of Ni in Example 1. This is mainly because the gas pressure used here was 200 Pa, which was slightly lower than 500 Pa in Example 1. According to the principle of inert gas condensation, the lower the gas pressure, the larger the mean free path of atoms and the lower the collision frequency. The probability of atoms colliding and merging multiple times in the gas phase is reduced, so the initial condensed particle size is smaller. Conversely, at 500 Pa, the chance of collision and merging increases, and the particle size is slightly larger. After infrared heat treatment at 900℃ for 5 min, the average grain size increased to 33 nm. The average grain size of Fe-Ni nanoclusters increased significantly from 13.3 nm to 33 nm after heat treatment at 900℃, far exceeding the increase of pure Ni at 800℃. The fundamental reason is that 900℃ corresponds to a higher reduction temperature of Fe-Ni alloy, which causes an exponential jump in the atomic diffusion and grain boundary diffusion coefficients compared to 800℃. At the same time, the Fe-Ni binary interdiffusion effect further enhances atomic rearrangement and grain boundary migration. At this temperature, the complete merging of particles and Ostwald ripening work synergistically to lead to a jump in grain size. The uniform infrared temperature field ensures that the growth process is synchronized throughout the entire range, avoiding abnormal coarsening. This result, together with Examples 1-3, constitutes a complete temperature control gradient from "almost unchanged" (500℃) to "mild growth" (600℃), "significant growth" (800℃), and "jumping growth" (900℃), verifying the ability of this method to control the in-situ grain size of multi-component alloy systems within a wide window.
[0056] Figure 5 For the statistical analysis of the particle size of the nano-Fe-Ni powder clusters prepared in this embodiment, from... Figure 5 It can be seen that the average grain size of the prepared Fe-Ni nanopowder clusters is 13.3 nm.
[0057] Figure 6 This example presents the particle size statistics of nano-Fe-Ni powder clusters treated at 900℃ in this embodiment. Figure 6 It can be seen that the average grain size of the Fe-Ni nanopowder clusters after infrared heat treatment at 900℃ for 5 min is 33 nm.
[0058] As described above, the particle size control of this invention follows a two-stage synergistic principle of "fine-tuning during preparation and precise control during heat treatment." In the preparation stage, the atomic collision frequency is controlled by finely adjusting the inert gas pressure, achieving a windowed preset of the initial particle size. The laser power must match the saturated vapor pressure of the target material to ensure evaporation efficiency and compositional consistency. In the heat treatment stage, temperature is the most sensitive parameter for precise particle size control: for Ni, the particle size remains almost unchanged at ≤500℃, moderate and controllable growth is achieved at 600℃, and the atomic diffusion coefficient increases exponentially at ≥800℃, triggering a synergistic effect of particle coalescence and Ostwald ripening to achieve significant growth; for Fe-Ni alloys, 900℃ further introduces an interdiffusion enhancement effect, achieving a leap in particle size. Infrared heating ensures a uniform temperature field, supplemented by short-time heat preservation and pre-pressing treatment, effectively guaranteeing narrowing of the particle size distribution and batch consistency.
[0059] In specific process implementation, the parameter window can be quickly selected according to the target particle size requirements using the following strategies: If only crystallinity treatment of powder clusters is required without changing the particle size, a low-temperature heat treatment not exceeding 500℃ is advisable to avoid grain coarsening caused by thermal activation; if a small, controllable increase in particle size is required, the temperature should be set around 600℃ with a short holding time (≤5 min); if a large-scale control of particle size is required, a high-temperature heat treatment exceeding 800℃ should be used. For multi-element alloy systems, in addition to temperature, the influence of laser power on the synchronicity of element evaporation must also be considered. Typically, a power increase of 10~20 kW compared to pure metal targets is required to ensure compositional conformation. The above principles provide a clear operational guide for the rapid selection of processes for different materials and particle size targets, avoiding the time-consuming and laborious parameter exploration in traditional trial-and-error methods.
[0060] This invention enables in-situ processing of nanopowders without exposure to the atmosphere throughout the entire process from preparation to heat treatment, effectively solving common problems of traditional methods such as uncontrollable particle size, easy agglomeration, impurity contamination, and poor batch stability. It can provide core material support for on-demand particle size design for high-end applications such as MLCC internal electrodes and fuel cell catalysts, possessing significant engineering application value and economic benefits.
[0061] The above are merely preferred embodiments of the present invention and are not intended to limit the invention in any way. Any simple modifications, alterations, and equivalent changes made to the above embodiments based on the technical essence of the present invention shall still fall within the protection scope of the present invention.
Claims
1. A method for in-situ control of nanopowder cluster particle size, characterized in that, This method involves controlling the particle size of nanoclusters of elemental metals, binary alloys, ternary and higher entropy alloys, amorphous alloys and ceramics prepared by inert gas condensation through in-situ heating. The method includes the following steps: Step 1: Place the bulk target material of the target component nanopowder clusters into a vacuum interconnected inert gas condensation system, and wait for the system vacuum to reach 10... -6 After Pa, an inert gas at a certain pressure is injected. Step 2: After liquid nitrogen is injected into the powder cluster collection cold trap, the picosecond laser heat source is turned on to bombard the target material by adjusting different powers. Step 3: Collect the powder using a rotating cold trap and scraper, and transfer the nanopowder clusters into the glove box using a built-in robotic arm; Step 4: In-situ heating treatment of nanopowder clusters at 600-1000℃ is carried out by building an infrared heating system in a vacuum or inert gas environment. Preferably, this step uses a glove box inert gas environment.
2. The method according to claim 1, characterized in that, In step one, the bulk target material is flexibly selected according to the composition of the target nanopowder, specifically including: pure metal targets such as nickel, copper, silver, platinum, gold, iron, cobalt, chromium, molybdenum or tungsten; binary alloy targets such as Ni-Fe, Cu-Ag, Pt-Ru or Au-Cu; ternary and above medium-high entropy alloy targets such as CoCrFeNi, AlCoCrFeNi or CrMnFeCoNi; amorphous alloy targets such as Pd-Ni-P, Zr-Cu, Ni-Mo-Nb or Fe-B; and ceramic targets such as SiC, Al2O3, TiO2 or ZnO. The density and purity of the target material directly affect the generation efficiency and compositional uniformity of nanoclusters. It is preferable to use a target material with a high density relative density ≥98% and a high purity ≥99.9%.
3. The method according to claim 1, characterized in that, In step one, the inert gas pressure ranges from 50 Pa to 5000 Pa; When the inert gas pressure is relatively low (50~2000 Pa), nanoclusters with smaller particle sizes are prepared. Under these conditions, the nanoclusters are larger than 10 nm and smaller than 15 nm. When the inert gas pressure is high, 2000~5000 Pa, nanoclusters with larger particle sizes are prepared. Under these conditions, the nanoclusters are larger than 15 nm and smaller than 20 nm. The inert gas pressure can be flexibly selected within this range according to the actual target particle size requirements in order to initially control the initial nanocluster particle size.
4. The method according to claim 1, characterized in that, In step one, the inert gas is helium, argon, or nitrogen.
5. The method according to claim 1, characterized in that, In step two, the power of the picosecond laser heat source bombarding the target material is 20~72 kW; a lower laser power of 20~50 kW can produce finer nanoclusters when used on targets with low melting points or easy evaporation; a higher laser power of 50~72 kW can be used on targets with high melting points or difficult evaporation to ensure sufficient evaporation rate and nanocluster yield.
6. The method according to claim 1, characterized in that, In step three, the water and oxygen content in the glove box is less than 1 ppm, and it is combined with contactless transfer by a robotic arm; the glove box is also equipped with oxygen and moisture sensors for real-time monitoring, and an automatic circulation and purification system is set up.
7. The method according to claim 1, characterized in that, In step four, the infrared heating device is built into the glove box. It uses the heating of the resistance wire to generate infrared radiation to achieve efficient heating. It can also achieve precise program control of the heating, heat preservation and cooling process, and supports multi-segment temperature curve settings. Its maximum heating temperature is 1000℃, which can meet the heat treatment requirements of most metal, alloy and ceramic nanopowders. Through in-situ infrared heating, the grain size of nanoclusters can be precisely controlled, thereby indirectly controlling the surface morphology and internal defects, and achieving precise in-situ control of particle size. The temperature can be monitored and adjusted in real time during the heating process, and the heating rate can be set arbitrarily in the range of 1~30℃ / min.
8. The method according to claim 1, characterized in that, In step four, before the heat treatment, the nanopowder clusters should be placed in a refractory material container and pre-treated by a micro press to ensure full contact of the powder.
Citation Information
Patent Citations
High vacuum interconnection system for nano powder preparation and in-site ultra-high pressure forming
CN110441100A
Method for preparing nano nickel powder by using plasma
CN119407182A
Nano nickel powder and preparation process thereof
CN121339465A
Infrared oven heating module structure
CN223448791U